Prospective study of efficacy and safety of non-ablative 1927 nm fractional thulium fiber laser in Asian skin photoaging - Li, Xianwen; Qin, Si; Shi, Siman; Feng, Yingjun; Li, Huarun; Feng, Yuqin; Li, Mujin; Wen, Ju (Frontiers in Surgery, 2023)
Background and Objective Photoaging manifests as deeper wrinkles and larger pores. It has been tried to rejuvenate photoaging skin using a variety of lasers, including fractionated lasers, which are a popular photorejuvenation treatment. A new breakthrough for skin rejuvenation is the 1927 nm fractional thulium fiber laser (FTL), a laser and light-based treatment option. Clinical data regarding the FTL for treating photoaging are limited despite its effectiveness and safety. This study is aim to evaluate FTL' clinical effectiveness and safety. Methods Fitzpatrick skin types II–IV subjects with mild to moderate photoaging signs were enrolled in this prospective study. At intervals of one month, patients received three full face treatments. Wrinkles, spots, texture, pores, melanin index, erythema index (MI and EI), skin elasticity and hydration were measured with non-invasive tool. The epidermal thickness and dermal density on ultrasonography were compared between baseline and one month after all treatment sessions. The Global Score for Photoaging scale (GSP) was rated by two independent evaluators at the baseline and final follow-up visit. Secondary outcomes included patient-rated pain on a 10-point visual analog scale (VAS), as well as overall satisfaction. Following each treatment, adverse events were noted. Results Totally 27 subjects (24 females and 3 males) with Fitzpatrick skin types II to IV and a mean age of 44.41 (range33–64) were enrolled. Results suggests that the epidermal thickness has significantly improved after treatment. Statistically significant improvements in melanin index, skin elasticity and wrinkles were noted. An analysis of 12 subjects' reports (44%) suggested their skin felt brighter. No post-inflammatory hyperpigmentation changes or adverse events were observed. 70% patients reporting “satisfied” or “extremely satisfied”. Conclusions In this study, FTL was found to be a safe and effective treatment option for treating photoaging.